2020
DOI: 10.1192/bjp.2020.89
|View full text |Cite|
|
Sign up to set email alerts
|

Are we repeating mistakes of the past? A review of the evidence for esketamine

Abstract: Summary Esketamine has been licensed for ‘treatment-resistant depression’ in the USA, UK and Europe. Licensing trials did not establish efficacy: two trials were negative, one showed a statistically significant but clinically uncertain effect, and a flawed discontinuation trial was included, against Food and Drug Administration precedent. Safety signals – deaths, including suicides, and bladder damage – were minimised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…A placebo-controlled relapse prevention trial has also demonstrated prevention of depressive relapse after acute treatment (Daly et al, 2019). However, the clinical validity and significance of these short, and longer term data together with ongoing uncertainty around the issues of abuse potential is still a matter of pointed debate (Horowitz and Moncrieff, 2020; Kryst et al, 2020; Mahase, 2020; Schatzberg, 2014; Sial et al, 2020). The trials of esketamine showed a similar pattern of side effects to those of ketamine including transient post dose hypertension and dissociation in a proportion of subjects.…”
Section: Treatmentsmentioning
confidence: 99%
“…A placebo-controlled relapse prevention trial has also demonstrated prevention of depressive relapse after acute treatment (Daly et al, 2019). However, the clinical validity and significance of these short, and longer term data together with ongoing uncertainty around the issues of abuse potential is still a matter of pointed debate (Horowitz and Moncrieff, 2020; Kryst et al, 2020; Mahase, 2020; Schatzberg, 2014; Sial et al, 2020). The trials of esketamine showed a similar pattern of side effects to those of ketamine including transient post dose hypertension and dissociation in a proportion of subjects.…”
Section: Treatmentsmentioning
confidence: 99%
“…Esketamine marketing authorization triggered a vivid debate and many concerns, mainly because of the lack of convincing evidence on its efficacy and safety, including the risk of misuse and suicide [3][4][5][6][7]. Currently, evidence on safety is almost entirely based on the development programs and approval trials [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, ( S )‐ketamine nasal spray of Johnson & Johnson was approved for treatment‐resistant patients with MDD although several concerns were addressed 28,29 . In contrast, ( R )‐ketamine did not cause psychotomimetic and dissociative side effects in healthy control subjects, whereas the same dose of ( S )‐ketamine produced these side effects in the healthy subjects 18 .…”
Section: Discussionmentioning
confidence: 99%